# How do you solve #5(-6-3d)=3(8+7d)#?

We use distribution to find a solution.

I hope this is useful.

By signing up, you agree to our Terms of Service and Privacy Policy

That is all. I hope this helps.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 5(-6-3d)=3(8+7d):

- Distribute the numbers inside the parentheses.
- Combine like terms on each side of the equation.
- Move all the terms involving the variable (in this case, d) to one side of the equation.
- Solve for the variable (d).

Here are the steps:

- (5(-6) + 5(-3d) = 3(8) + 3(7d))
- (-30 - 15d = 24 + 21d)
- Add 15d to both sides: (-30 = 24 + 36d)
- Subtract 24 from both sides: (-54 = 36d)
- Divide both sides by 36: (d = -\frac{3}{2})

So, the solution to the equation is (d = -\frac{3}{2}).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7